2023
DOI: 10.1038/s41612-023-00423-1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of accelerated warming in Mediterranean climate-type regions

Abstract: The near-surface temperature in Mediterranean climate-type regions has increased overall similarly or more rapidly than the global mean rates. Although these regions have comparable climate characteristics and are located at similar latitudes, recent warming acceleration is most pronounced in the Mediterranean Basin. Here, we investigate the contributions of several climate drivers to regional warming anomalies. We consider greenhouse gases, aerosols, solar irradiance, land–atmosphere interactions, and natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Nevertheless, compared to the downward trend in scatterers (SAOD) in the atmosphere, the upward trends in DAOD and AAOD suggest an increasingly larger rise in dust and absorbing particles. A recent study also noted the declining trend in TAOD over the Mediterranean [32]. Raptis et al [95] found a −1.7% trend per year for TAOD 440 over Athens, Greece, in the period 2008-2018; this value is −0.72% per year in our case.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, compared to the downward trend in scatterers (SAOD) in the atmosphere, the upward trends in DAOD and AAOD suggest an increasingly larger rise in dust and absorbing particles. A recent study also noted the declining trend in TAOD over the Mediterranean [32]. Raptis et al [95] found a −1.7% trend per year for TAOD 440 over Athens, Greece, in the period 2008-2018; this value is −0.72% per year in our case.…”
supporting
confidence: 75%
“…In a study from the 1980s, Ropelewski and Halpert [31] found a close relationship between the El Niño phases and the precipitation patterns over Australia, the Americas, the Indian sub-continent, and Africa. On the other hand, Urdiales-Flores et al [32] showed that the Mediterranean Basin bas been warming, over the last 120 years , more rapidly than the global rate; they attributed this warming amplification to the combined effect of reduced aerosol loading and a decrease in soil moisture over the region. Chiacchio and Wild [33] attributed the all-sky solar radiation changes over Europe in the period 1970-2000 to the NAO and more specifically to the cloud-cover variability associated with the NAO phases; they also indicated the role of aerosols in this process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current climatic changes around the glob are largely blamed on global warming which is caused by the accumulation of greenhouse gases in the atmosphere, primarily from human activities such as burning fossil fuels (coal, oil, and natural gas), deforestation, and industrial processes 55 . While the impacts of global warming can vary based on geographic location, socioeconomic factors, and regional policies, many Arab countries may be particularly susceptible to its effects because they exist in regions characterized by arid or semi-arid climates, such as the MENA region.…”
Section: Resultsmentioning
confidence: 99%
“…Some Arab countries face political instability and conflict, which can hinder their ability to address the impacts of global warming effectively 55 . Additionally, socioeconomic factors may impact a country's capacity to invest in climate adaptation and mitigation strategies.…”
Section: Resultsmentioning
confidence: 99%